2018
DOI: 10.1080/22797254.2018.1442179
|View full text |Cite|
|
Sign up to set email alerts
|

Comparing support vector machines with logistic regression for calibrating cellular automata land use change models

Abstract: Cools & Jacques Teller (2018) Comparing support vector machines with logistic regression for calibrating cellular automata land use change models,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 59 publications
0
24
0
1
Order By: Relevance
“…A negative correlation with the proximity drivers from roads is also expected, because the probability of expansion in the vicinity of existing roads, is generally higher (Hu & Lo, 2007;Luo & Wei, 2009;Mustafa, Rienow, et al, 2018).…”
Section: Builtup Causative Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A negative correlation with the proximity drivers from roads is also expected, because the probability of expansion in the vicinity of existing roads, is generally higher (Hu & Lo, 2007;Luo & Wei, 2009;Mustafa, Rienow, et al, 2018).…”
Section: Builtup Causative Factorsmentioning
confidence: 99%
“…The ( ) , the neighborhood effect, was evaluated through a 3x3 moving window. It will be determined using the CA approach, with the method proposed by White &Engelen (1997, andalready applied in Mustafa, Heppenstall, et al (2018), expressed with Eq c. Mustafa, Rienow, et al, (2018), Chen et al, (2014) and Poelmans & Van Rompaey, (2009) examined several square sizes and found that the model runs with the 3x3 neighborhood moving window and produced a land-use pattern that best fits the actual pattern. Furthermore, Mustafa, Rienow, et al, (2018) used a 100 m resolution, similar to that of this research, and found that a 3x3 neighborhood moving window outperformed other window sizes (5x5, 7x7, 9x9, and 11x11).…”
Section: Transition Potential and Calibration Processmentioning
confidence: 99%
“…CA is a spatial pattern of each landscape unit each land as a cell, and its specific evolutionary rules determine how it self-organizes in space and its spatial dependence to simulate changes in land use [55]. The evolution rules of CA depend on the influence of the grids and their neighbors, so the attributes and locations of the grid are factors that influence land use [56,57].…”
Section: Autocorrelationmentioning
confidence: 99%
“…In addition, machine learning algorithms have been used extensively to explain LULCs. Several researches had combined Cellular automata (CA) with a plethora of modeling frameworks such as Markov chains [10], neural networks [11] support vector machines [12] and kernel-based methods [13] among others. More recently, CA have been successfully combined with Random Forest [14,15].…”
Section: Introductionmentioning
confidence: 99%